Isorhynchophylline attenuates proliferation and migration of synovial fibroblasts via the FOXC1/β-catenin axis - Yingyi Wu; Yan Bian; Jing Fei; Yang Huang (Taylor & Francis Group, 2023)
AbstractRheumatoid arthritis (RA) is a common type of chronic inflammatory disease. Elucidating the mechanism of fibroblast-like synovial (FLS) as a pathologic factor in RA may address the urgent medical requirement for the treatment of RA. Isorhynchophylline (IRN) is a tetracyclic hydroxyindole alkaloid isolated from uncinaria, which has multiple biological activities and affects the progression of osteoarthritis. However, the role of IRN in rheumatoid arthritis remains unclear. Herein, our study aimed to elucidate the potential effect of IRN on RA and reveal its mechanism. Human FLS cell line MH7A cells were stimulated with TNF-α for 24 h to construct a cell model. CCK-8, Edu, wound healing, as well as transwell assays were conducted to detect the effects of IRN on cell proliferation and motility. ELISA and Immunoblot assays were further performed to detect the production of pro-inflammatory factors and the expression levels of MMPs. Immunoblot and Immunostaining assays were conducted to uncover the mechanism. ELISA, H&E staining, and Immunoblot assays were used to confirm the effects of IRN on RA in a CIA rat model. We revealed that IRN restrained TNF-α-stimulated MH7A cell proliferation and motility. In addition, IRN blocked the production of pro-inflammatory factors and MMPs in TNF-α-stimulated-MH7A cells. We further found that IRN restrained FOXC1/β-catenin axis, and improved MH7A cell proliferation as well as migration via the FOXC1/β-catenin axis. IRN restores CIA by inhibiting pro-inflammatory cytokines in synovial tissues. In summary, IRN attenuates proliferation and migration of FLS in RA via the FOXC1 mediated β-catenin axis.